Application of Islamic Teachings on Brotherhood to Ease Fuel Subsidy Removal Challenges Among Vulnerable Nigerians - Muhammad, Adamu Abubakar; Idriss, Ibrahim Dahiru; Ardo, Adam Muhammad; Salisu, Muhammad Auwal (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2023)
This paper examines the application of Islamic teachings on brotherhood to ease fuel subsidy removal challenges among Nigerians. Drawing on Islamic texts and the existing literature on the role of brotherhood in alleviating socio-economic tensions, this research opens a new perspective for understanding how Islamic principles can be used to create a more just and equitable society. A qualitative research methodology was employed, and the data were gathered through a review of the related literature and a semi-structured interview with pertinent bodies, as well as content analysis for analyzing the data. The paper finds that, based on Islamic teachings, brotherhood is an essential element in cultivating a sense of solidarity and belonging amongst Nigerians. These feelings assist in lessening the effects of fuel subsidy removal and allow for a more comprehensive approach to tackling the resulting economic and socio-cultural challenges. Finally, the paper proposes a number of policy recommendations to utilize Islamic teachings of brotherhood to create a more equitable society in Nigeria